(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Public speaking anxiety remains a barrier that can hinder students’ ability to convey ideas and actively participate during the learning process. One factor thought to play a role in reducing this anxiety is self-efficacy, which is an individual’s belief in their ability to face a task or situation. This study aims to analyze the effect of self-efficacy on public speaking anxiety in grade X students of SMA Negeri X Bukittinggi in 2026. The study used a quantitative approach with a correlational method. The research sample consisted of 115 students selected through a random sampling technique. Data were collected using a self-efficacy scale based on Bandura’s (1997) theory and a public speaking anxiety scale based on Bodie’s theory, then analyzed using simple linear regression with the help of SPSS. The results showed that self-efficacy had a negative and significant effect on public speaking anxiety (t = -5.698; p = 0.002). This finding indicates that students who have higher confidence in their abilities tend to experience lower levels of anxiety when speaking in public. The research results emphasize the importance of strengthening self-efficacy as a strategy to increase self-confidence and support students’ communication skills in the school environment